Circulating Tumor Cells in Metastatic Breast Cancer: From Genome Instability to Metastasis - Ivanova, Ekaterina; Ward, Ambber; Wiegmans, Adrian P.; Richard, Derek John (Frontiers in Molecular Biosciences, 2020)
The emergence of clinical resistance in repeatedly treated cancers extends from the primary tumour’s capability to exploit genome instability to adapt, escape and progress. Triple negative breast cancer serves as a good example of such a response demonstrating poor clinical outcome due to a high rate of cellular heterogeneity resulting in metastatic relapse. The capability to effectively track the emergence of therapeutic resistance in real-time and adapt the clinical response is the holy grail for precision medicine and has yet to be realised. In this review we present liquid biopsy using CTCs and ctDNA as a potential replacement and/or addition to the current diagnostic tests to deliver personalised therapies to patients with advanced breast cancer. We outline current uses of liquid biopsy in the metastatic breast cancer setting and discuss their limitations. In addition, we provide a detailed overview of common genome instability events in patients with metastatic breast cancer and how these can be tracked using liquid biopsy.